Eating Behaviors Motives Underlying Food Selection and Perceived Barriers to Healthy Eating Among Adolescents in Alexandria-Egypt - Mohammed, Neama Yousef; Elkaluby, Eman Ahmed; Mohamed, Ahlam Mahmoud (International Journal For Research In Health Sciences And Nursing, 2019)
Background: Adolescents may have an enormous appetite at times. Generally, if they are eating a healthy, balanced diet they will have an appropriate weight, while eating too much or too much of unhealthy food can lead to overweight. Similarly, not eating enough can also lead to issues of being underweight which can affect energy levels, growth and development. It may also mean missing important nutrients such as iron and calcium. Aim: The study aimed to assess eating behaviors motives underlying food selection and perceived barriers to healthy eating among adolescents in Alexandria Egypt. Study design: Descriptive design was used to carry out this study. Study setting: The study was conducted at 8 youth centers in Alexandria governorate. Study tools: three tools were used for data collection from the adolescents namely: Tool I: Motive underling the selection of food: The Food Choice Questionnaire (FCQ), Tool II: Alarming Eating Behaviors Assessment Questionnaire, and Tool III: Perceived barriers to healthy eating assessment questionnaire in addition to Socio-demographic Characteristics of the studied adolescents. Study subjects: The study subjects consisted of 227 adolescents from the above-mentioned settings. Results: The findings of the present study revealed that sensory appeal comes as the first priority motive followed by mood, health, and weight control, whereas familiarity followed by convenience, natural content, ethical concern, and the price comes at the last ranking of the healthy eating motives from the studied adolescent perspectives. Additionally, the higher mean percent score was belonging to the social barriers with a mean of 63.2±25.5, compared to personal and environmental barriers with a mean of 46.0±22.0. Regarding the alarming eating behaviors among the studied adolescents around one third only of the studied adolescents always committed to daily breakfast intake, more than half of the studied adolescents reported that they always eat outside their home and eating in front the television or while using computer or cellular phone, drinking tea after meal. Less than a quarter only of the studied adolescents received low salty foods. More than one fifth of the studied adolescents declared that they sometimes or always eat a heavy meal at dinner. Only 30.0% of the studied adolescents didn’t sleep after dinner by less than two hours. More than two fifths of the studied adolescents reported that they always received three sugary drinks per day. Conclusion: There are nine motives affecting the studied adolescent decision to select healthy food and there are two main barriers against healthy eating practices. Recommendation: A well planned session must be conducted to orient the adolescents about healthy eating barriers and motives as one of the basic roles of the community health nurses.